Factors associated with participation by African Americans in a study of the genetics of glaucoma. Issue 6 (18th August 2019) - Parikh, Rupin; O'Keefe, Laura; Salowe, Rebecca; Mccoskey, Makayla; Pan, Wei; Sankar, Prithvi; Miller-Ellis, Eydie; Addis, Victoria; Lehman, Amanda; Maguire, Maureen; O'Brien, Joan
ABSTRACT: Objective: African Americans have been historically underrepresented in research studies. Our aim was to evaluate factors influencing enrollment in the Primary Open-Angle African American Glaucoma Genetics (POAAGG) study. Design: Patients approached to enroll in the POAAGG study were asked to complete a 15-item survey addressing demographic characteristics, knowledge of genetics and glaucoma, and opinions on human research. Survey responses were compared between subjects who enrolled (Enrollers) and did not enroll (Decliners) in the POAAGG study. Results: Enrollers ( N  = 190) were 3.7 years younger ( P  = 0.007) and had similar gender, education, and income level to Decliners ( N  = 117). Knowledge about genetics and glaucoma was similar between groups. Enrollers were more comfortable providing DNA for research studies (93.1% vs 54.1%; P  < 0.001) and more likely to have participated in prior studies ( P  = 0.003) and consider participating in future studies ( P  < 0.001). Among Decliners, lack of time was the primary reason given for not enrolling. Conclusion: To increase participation of African Americans in genetic research studies, efforts should be made to raise comfort with DNA donation.